Patient satisfaction in pediatric outpatient settings from the parents' perspective - The Child ZAP: A psychometrically validated standardized questionnaire - Bitzer Eva; Volkmer Stephanie; Petrucci Marco; Weissenrieder Nikolaus; Dierks Marie-Luise (BMC, 2012)
Abstract Background Patient surveys constitute a valuable source of information in patient-focused health care. The objective of this study was to develop and validate a standardized, patient centered, quantitative instrument to assess parent satisfaction in ambulatory pediatric care to be used in quality management and benchmarking activities, the Child-ZAP. Methods A preliminary version of the survey (38 items) was conducted in n = 19 pediatric practices. After psychometric testing a modified Child-ZAP was tested in a second survey (n = 20 new pediatric practices). Data from n = 979 patients were available for analysis. Results The final version of the Child-ZAP contains eight dimensions, three "Child-Scales" and five "Parent-Scales". Confirmatory factor analysis confirms the three hypothesized child dimensions as well as the five parent dimensions. The factorial structure is confirmed in subgroups of younger and older children. Conclusions With satisfactory to good results for validity and reliability testing, the final Child-ZAP is applicable in pediatric ambulatory care for children of all age groups.